How to assess the efficiency of the agro waste disintegration process. Issue 25 (10th November 2021) - Zubrowska-Sudol, Monika; Walczak, Justyna; Garlicka, Agnieszka; Sytek-Szmeichel, Katarzyna; Umiejewska, Katarzyna
ABSTRACT: The objective of the study was to verify whether the method of determining the efficiency of sewage sludge disintegration, i.e. the disintegration degree (DD), can also be used to assess agro-waste disintegration. The following types of agro waste were tested: remains of fruits, sugar beet pulp and sugar beet pulp in the form of pellets. It was shown that DD as used for sewage sludge can also be a useful tool in assessing the disintegration efficiency of agro waste, although it requires the following modifications: (a) a methodology of chemical hydrolysis for each type of agro waste in order to determine the total amount of soluble COD (SCOD) that can be released from the sample and (b) possible changes in the SCOD value that may occur in the sample left in ambient conditions for a time period corresponding to the duration of the disintegration process. DD of agro waste determined according to the formula adopted for sewage sludge resulted in a considerable overestimation of the value in comparison to the formula proposed by the authors, i.e. DD determined for an energy density of 35 kJ L −1 was higher by 55.9 ± 21.5%, and for an energy density of 140 kJ L −1 it was higher by as much as 73.8 ± 28.1%. Taking into account the differences in the determined disintegration degree values that result from the methodology of conducting the chemical hydrolysis, it is recommended, in order to assess the efficiency of disintegration of agro waste, to use the efficiency of organic compound release. GRAPHICAL ABSTRACT: UF0001